EFEITO DO EVENTO MON88017 (Cry3Bb1), DE INSETICIDA E DA ÉPOCA DE SEMEADURA NA REDUÇÃO DO DANO DE Diabrotica speciosa (GERMAR, 1824) (COLEOPTERA: CHRYSOMELIDAE) NA RAIZ DO MILHO - Gallo, Paulo (2012)
The presence of Diabrotica speciosa larvae causes damage to corn root system and reduction in grain yield, mainly in second season crops. Applying insecticide in the seed furrow can be effective, but this assumes a form of preventive control and implies higher production costs and environmental impact. We evaluated the efficacy of genotypes AG7000RW and DKB330RW (Cry3Bb1) and their isolines to reduce the damage caused by D. speciosa larvae to corn root system, the efficacy of the insecticide fipronil applied in the furrow, and the effect of the interaction of both treatments on the yield of maize hybrids, as well as the planting date when the most severe damage occurs. The efficacy experiment was carried out in Itaberá, SP, in no-till planting system after oat crop. The damage to the roots was evaluated 52 days after emergence, using a visual score according to its intensity. Stalk lodging was determined by counting the plants leaning more than 25º in relation to its own axis at harvest. Genotypes AG7000 and DKB330 with no insecticide application presented damage and the resulting scores were 1.62 and 1.85, whereas the scores of their Bt isolines were 0.25 and 0.24, respectively. Genotypes AG7000 and AG700RW had the highest percentage of matter and amount of dry root in relation to DKB330 and DKB330RW, regardless of insecticide application. Stalk lodging of 46.7% found in non-Bt genotype DKB330 with no insecticide application reflected negatively on the yield of this treatment. In contrast, with insecticide application, stalk lodging ranged from 0.2% to 2.2% between genotypes, not influencing their yield. Cry3Bb1 protein was effective in reducing the damage to the root regardless of the genotype tested. Genotypes with high yield potential and lower root mass may present higher yield response when protected by the toxin or insecticide in the presence of a large larval population. In the 2010/2011 season, we assessed the damage in non-Bt corn root at four planting dates in Itaberá (10/14, 11/3, 11/25, and 12/20) and three in Castro, PR (9/29, 10/21, and 11/11). In the following season, 2011/2012, we evaluated six planting dates in Itaberá (9/21, 10/18, 11/21, 12/28, 1/30, and 2/20) and four in Castro (9/20, 10/10, 10/30, and 11/20). We observed that, from the second planting date on, the root damage reached scores over 3.0 and remained above 4.0 in all other planting dates in Itaberá in both seasons. In Castro, only the seeding performed in 11/20/2011 reached a score above 3.0. The use of protection in corn root, by applying insecticide or toxin, presented a greater response in sowing carried out from October on in the region of Itaberá.